Public policy for housing development: a case study on housing development in Semarang Regency - Indonesia - Gatot Sasongko; Ina Ariani Restiani Hunga; Ardhian Syah Noer Julana; Yustinus Wahyudi; Paulus Leliak; Andrian Dolfriandra Huruta (Insights into Regional Development)
This study aims to describe the implementation of public policy from the perspective of Dye's theory of spatial planning for housing in Semarang Regency. The primary data used in this study were obtained from ten informants as the representatives of each business activity who proposed location permits for housing activities. While the secondary data were obtained from the Public Works Office of Semarang Regency. The results show that there were ten investment activity plans for housing in Semarang Regency, whose proposals were not approved initially by the relevant agencies because they were not in accordance with the provisions of spatial planning. This study provide evidence from ten informants there are eight cases as follows space utilization through a land consolidation program, space utilization in a wide & river border area, space utilization in vacant spatial planning area, space utilization for communities affected by railroad project, space utilization in spatial planning area of crop farming, space utilization with a housing certificate status, space utilization in plantation planning area, and space utilization in the vacant spatial planning area adjacent to the border of other city administration area. However, after being considered by the government in terms of public policy, the ten location permits were issued with certain conditions. Thus, it could be concluded that the public policy was essentially designed by the government to guarantee and fulfill the needs of the community in conducting investment activities such as housing developers.